Fiber-THz-Fiber Link for THz Signal Transmission - Can Wang; Jianjun Yu; Xinying Li; Pengqi Gou; Wen Zhou (IEEE Photonics Journal)
We propose and experimentally demonstrate vector signals seamless integration delivery over fiber-THz-fiber link. Up to 13 Gb/s quadrature-phase-shift-keying signals are transmitted over 10 km single mode fiber-28 (SMF-28), 3.8 m wireless link, and 2.2 km SMF-28 link. At the transmitter, we use a photonics-aided scheme to generate 450 GHz THz signal. While at the receiver side, we employ analog down-conversion by one electrical mixer, and then the down-converted signals are used to drive one directly modulated laser to realize electrical-to-optical conversion.